Chronic pain management in fibromyalgia: the INTEGRO (INTEGRated Psychotherapeutic InterventiOn) protocol and its application on two case studies - Pasini, Ilenia; Donisi, Valeria; Veneziani, Elisa; Perlini, Cinzia; Nizzero, Marta; Lippolis, Irma; Polati, Enrico; Schweiger, Vittorio; Del Piccolo, Lidia (Frontiers in Medicine, 2024)
Objectives To present an innovative integrated manualized psychotherapeutic intervention for fibromyalgia (FM) based on cognitive and behavioral therapy, acceptance and commitment therapy, and somatic experiential techniques (namely the INTEGRated Psychotherapeutic InterventiOn, INTEGRO) and illustrate its application on two case studies. Methods INTEGRO is composed of 12 individual sessions. The main objectives of the intervention were psychoeducation of chronic pain mechanisms, understanding the role of cognitive and emotional variables in one’s pain perception, teaching patient-tailored skills to increase pain awareness and its management, and learning how to live with pain experience. A 57-year-old woman (patient A) and a 26-year-old woman (patient B) with FM have been selected to describe their care pathways connected to the INTEGRO protocol. Data related to assessment variables and clinical processes have been reported, focusing on the mechanisms that contribute to the maintenance (i.e., avoidance or overcompensation) of chronic pain in FM, on the role of patients’ naïf theories, and on the implications that all these aspects may have on the burden related to pain management. Results Both patients showed a reduction in FM burden and an increase in self-efficacy in pain management: patient A reported an improvement in emotional regulation ability; patient B showed a decrease in pain interference in work activities and on emotional dimension. Conclusion Examining each phase of the clinical protocol through the lens of its clinical application, the paper provides insights into the relationship among crucial psychosocial mechanisms, pain perception, management in FM treatment, and how all these aspects have been dealt with during psychotherapeutic treatment.